Bibliometric Insights into Flipped Classroom Implementation in K-12 Education - Judijanto, Loso; Handayani, Noor Fazariah; Saputra, Dedi Gunawan (The Eastasouth Journal of Learning and Educations, 2024)
This study employs bibliometric analysis to map the evolution and dissemination of flipped classroom methodologies in educational research, with a focus on its implementation in K-12 and higher education. Using VOSviewer to analyze data extracted from major academic databases, we identified key trends, collaborations, and thematic concentrations within the literature from 2004 to 2023. The results highlight the flipped classroom as a central node interconnected with digital education technologies such as MOOCs and online learning platforms, indicating its pivotal role in transforming traditional educational paradigms into more student-centered approaches. The analysis reveals a strong link between flipped classrooms and improved engagement and adaptability in various educational settings, emphasizing the model's versatility. However, gaps remain in equitable access to technology and comprehensive assessments of long-term impacts, suggesting directions for future research and policy development. This study provides foundational insights for educators, policymakers, and researchers aiming to optimize and expand flipped classroom practices.